Research progress on implant-supported telescopic overdenture - HE Yun; ZHOU Yi (Kouqiang hemian waike zazhi)
Implant-supported telescopic overdenture is a type of implant-supported overdenture characterized by high technical complexity and intricate procedures. Despite these challenges, it has the potential to yield satisfactory outcomes and presents promising prospects. This paper reviews its research progress on three key aspects: Concept and classification, advantages and disadvantages, and clinical applications. The current research findings are synthesized to provide insights into the future directions of research in the field of implant-supported telescopic overdentures.